Tunisia : Third Review Under the Stand-by Arrangement, Request for Modification of Performance Criteria and Waivers of Applicability. (IMF Staff Country Reports; Country Report ;, 2014)
EXECUTIVE SUMMARY Context. On June 7, 2013, the Executive Board approved a 24-month SBA in an amount equivalent to 400 percent of quota (SDR 1.15 billion or about USD 1.75 billion). To date, SDR 427.92 equivalent to USD 659 million has been disbursed. The pillars of the program are to: (i) achieve short-term macroeconomic stability; (ii) lay the foundation for stronger and more inclusive growth; and (iii) protect the most vulnerable. Background. The adoption of a new constitution and the formation of a new technocratic government in January 2014 led to greater confidence on political prospects and economic reforms. Growth has been moderate and remains insufficient to bring down unemployment significantly in the short term. At the same time, external and fiscal imbalances remain high, while demands for higher wages and additional jobs are rising. The program is broadly on track. Two out of three 2013 end-December quantitative performance criteria (QPC) targets have been missed, but by a smaller margin than originally envisaged, and all end-March 2014 QPCs are expected to be met. Progress on the structural reform agenda has been slowed by last year's political crisis and the transition between governments. Program strategy. Containing current expenditures, and pursuing prudent monetary policy and greater exchange rate flexibility are essential to contain high external and fiscal deficits and to build investors' confidence. Improved banking regulation, a strategic orientation of public banks, and strengthened supervision will help reduce banking sector fragilities, which are currently hampering private sector development. Scaling up public investments, reforming tax policy and revenue administration, accelerating public enterprise reform, and protecting the most vulnerable will help lay the foundations for more inclusive growth and level the playing field for investors. Risks to program implementation are important. Main risks relate to regional and domestic security tensions, set-backs in the political transition, and weaker economic activity in major trading partners. Successful implementation of the Fund-supported program will be contingent on the government's ability to garner consensus among political parties backing it and on its capacity to push reforms through vested interests. The completion of the third review will make SDR 145.08 million (about USD 225 million) available.